2014
DOI: 10.3892/br.2014.356
|View full text |Cite
|
Sign up to set email alerts
|

Association between fetuin-A levels with insulin resistance and carotid intima-media thickness in patients with new-onset type 2 diabetes mellitus

Abstract: Abstract. Fetuin-A, which is known to inhibit insulin signaling and pathological calcification, has emerged as a diabetes risk biomarker. In the present study, the association between the fetuin-A levels with insulin resistance (IR) and carotid intima-media thickness (CIMT) was investigated in patients with new-onset type 2 diabetes mellitus (nT2DM). A total of 100 patients with nT2DM (nT2DM group) and 100 normal glucose tolerance (NGT group) controls were evaluated. The serum fetuin-A level was measured by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The previously reported positive association of circulating fetuin-A with BMI referred to populations with a wide range of BMI, including not only obese patients, but also lean or overweight individuals. [6][7][8][9] Thus, the fact that our study only evaluated subjects with BMI ≥35 kg/m 2 may have limited the potential for detection of significant associations between circulating fetuin-A and indices of obesity across the relatively narrow range of BMI of our study. Similarly, Himmetoglu et al found that although circulating fetuin-A was higher in morbidly obese patients compared with lean or overweight controls, it was not correlated with BMI in the subgroup of morbidly obese individuals.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The previously reported positive association of circulating fetuin-A with BMI referred to populations with a wide range of BMI, including not only obese patients, but also lean or overweight individuals. [6][7][8][9] Thus, the fact that our study only evaluated subjects with BMI ≥35 kg/m 2 may have limited the potential for detection of significant associations between circulating fetuin-A and indices of obesity across the relatively narrow range of BMI of our study. Similarly, Himmetoglu et al found that although circulating fetuin-A was higher in morbidly obese patients compared with lean or overweight controls, it was not correlated with BMI in the subgroup of morbidly obese individuals.…”
Section: Discussionmentioning
confidence: 84%
“…Regarding the relationship of circulating fetuin-A with body weight status, although most of the studies have found a positive association between circulating fetuin-A and body mass index (BMI) and a reduction of serum fetuin-A levels after weight loss, some studies reported conflicting results. [6][7][8][9][10][11][12][13][14][15][16] Bariatric surgery is a weight loss intervention achieved via an alteration not only of the passage of food through the gastrointestinal tract, but also of the secretion of gut hormones regulating appetite. 17 Moreover, among weight loss interventions the magnitude of weight reduction after bariatric surgery is by far the greatest.…”
mentioning
confidence: 99%
“…In an another study, authors found increased levels of fetuin-A in patients with new onset type 2 diabetes mellitus compared with individuals who had normal glucose tolerance test. They also found correlation between serum fetuin-A levels and glycated insulin [25]. For being an important mediator in calcified matrix metabolism, fetuin-A is also associated with bone mineral density.…”
Section: Discussionmentioning
confidence: 84%
“…Diabetes mellitus (DM) is a type of chronic metabolic disease involving the interaction of genetic and environmental factors. It is characterized by dysinsulinism, insulin resistance (IR) and disorders of the blood sugar, lipid and protein metabolisms (1). An increase in the prevalence rate of DM in China is reported to be due to the economic development and increase in the average life expectancy (2).…”
Section: Introductionmentioning
confidence: 99%